2010
DOI: 10.1108/01443571011075074
|View full text |Cite
|
Sign up to set email alerts
|

How do companies achieve mix flexibility?

Abstract: Purpose -The purpose of this paper is to address a research gap relating to the understanding of how one type of manufacturing flexibility -mix flexibility -is achieved during day-to-day operations. Design/methodology/approach -Constructs from coordination theory are used in order to understand the way in which physical manufacturing resources are coordinated during daily operations to produce a company's product mix. A multiple case study methodology is used to investigate the applicability of these construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The concept of coordination has been discussed widely in the literature. Within organizations, actions carried out by one division in a system can directly or indirectly affect the actions or outcomes of another division in a system which requires coordination mechanisms that are employed to manage these dependencies between these different systems (Wilson and Platts, 2010).In today's dynamic and competitive manufacturing environment, labour flexibility and teamwork are considered as central pillars to achieve flexibility and have high effect on manufacturing environment (Fraser, 2010). To alleviate supply risks and develop competitive advantage, supply professionals need to synchronise the relationships in the supply chain and increase the flow of information and communication efforts (Larry et al, 2004).…”
Section: Collaborative Effortsmentioning
confidence: 99%
“…The concept of coordination has been discussed widely in the literature. Within organizations, actions carried out by one division in a system can directly or indirectly affect the actions or outcomes of another division in a system which requires coordination mechanisms that are employed to manage these dependencies between these different systems (Wilson and Platts, 2010).In today's dynamic and competitive manufacturing environment, labour flexibility and teamwork are considered as central pillars to achieve flexibility and have high effect on manufacturing environment (Fraser, 2010). To alleviate supply risks and develop competitive advantage, supply professionals need to synchronise the relationships in the supply chain and increase the flow of information and communication efforts (Larry et al, 2004).…”
Section: Collaborative Effortsmentioning
confidence: 99%
“…Frayret et al (2004) identified three coordination mechanisms used to manage shared resources: direct communication, rules-of-the-game to manage prescribed and forbidden actions; and market-based pricing and bidding mechanisms. In a study dealing specifically with mix flexibility achievement in the flour milling industry, Wilson and Platts (2010) identified a number of coordination mechanisms used to manage shared producer or processing activities, shared transfer line activities and shared consumer or packaging activities, as shown in Table I.…”
Section: Shared Resources and MIX Flexibility Achievementmentioning
confidence: 99%
“…Continuing with this line of reasoning, Wilson and Platts (2010) argued that mix flexibility is achieved, at an operational level, through the use of coordination mechanisms to manage the dependencies relating to mix flexibility. In a study of mix flexibility achievement in the flour milling industry, Wilson and Platts (2010) went on to identify a number of these coordination mechanisms used to manage shared resources.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wilson and Platts (2010) addressed the question of how mix flexibility is achieved during day-to-day operations, and found that at operational level, mix flexibility is achieved through shared resources, floor dependency, and simultaneity constraints. In another study, Hallgren and Olhager (2009), investigated the relationship between volume and product mix flexibility.…”
Section: Organizational Flexibilitymentioning
confidence: 99%